Crystal structure of bis(acetophenone 4-benzoylthiosemicarbazonato-κ2 N1,S)nickel(II) - Kadir, Faraidoon Karim; Shamsuddin, Mustaffa; Rosli, Mohd Mustaqim (International Union of Crystallography, 2016)
In the asymmetric unit of the title complex, [Ni(C16H14N3OS)2], the nickel ion is tetracoordinated in a distorted square-planar geometry by two independent molecules of the ligand which act as mononegative bidentate N,S-donors and form two five-membered chelate rings. The ligands are in trans (E) conformations with respect to the C N bonds. The close approach of hydrogen atoms to the Ni2+ atom suggests anagostic interactions (Ni H—C) are present. The crystal structure is built up by a network of two C—H O interactions. One of the interactions forms inversion dimers and the other links the molecules into infinite chains parallel to [100]. In addition, a weak C—H interaction is also present.